Associations of statin use with the onset and progression of open-angle glaucoma: A systematic review and meta-analysis. (April 2022) - Yuan, Yixiong; Xiong, Ruilin; Wu, Yi; Ha, Jason; Wang, Wei; Han, Xiaotong; He, Mingguang
Summary: Background: Statins, the first-line therapy for hyperlipidemia, have received considerable attention as candidates for glaucoma treatments given its neuroprotective effects. In this systematic review and meta-analysis, we intended to assess the association of statin use with the onset and progression of open-angle glaucoma (OAG). Methods: Databases including PubMed, Embase and Web of Science Core Collection were searched for longitudinal studies reporting the association between statin use and OAG onset or progression on Feb 3, 2021. A meta-analysis was performed for the association between statin use and OAG onset. Relative risks (RRs) with 95% confidential intervals (CIs) were retrieved from included studies and pooled using random-effects models. Potential risks of bias were evaluated by the Newcastle-Ottawa Quality Assessment Scale for all eligible studies. This study had been registered on PROSPERO (CRD 42021232172). Findings: 515, 788 participants (mean age 68.7 years, 62.3% female) from ten studies were included in the systematic review of the association between statin use and OAG onset, and 26, 347 OAG patients (mean age 67.3 years, 52.2% female) from seven studies were included for the association between statin use and OAG progression. Potential risks of bias were detected in 12 studies, which were mainly attributed to selection and confounding bias. In addition, 515, 600 participants from eight studies were included in the meta-analysis which collectively showed that statin use was associated with a reduced risk of OAG onset (Pooled RR: 0.95; 95%CI: 0.93–0.98; I 2 =0.199;). No significant heterogeneity or publication bias was found for studies included in the meta-analysis. There were inconsistent evidences for the association between statin use and OAG progression. Interpretation: Statin use is associated with a slightly lower risk of OAG onset based on existing evidences from longitudinal observational studies, the association between statin use and OAG progression remains inconclusive. The included evidences were typically weak due to poor study design and under-powered studies. Current findings should be interpreted cautiously and still need to be validated in further research. Funding: The National Key R&D Program of China (2018YFC0116500), Science and Technology Planning Project of Guangdong Province (2013B20400003), the China Postdoctoral Science Foundation (2019TQ0365), the National Natural Science Foundation of China (82000901 and 82101171).